Are we at a turning point in journal assessment? An introduction to altmetrics - Krauskopf, Erwin (Austral Journal of Veterinary Sciences, 2020)
The status of any journal in which research is published is an important issue for academics. For many years the impact factor has been the criteria of choice to infer the quality of the research being published by each journal. However, with the massification of the internet, research currently impacts well beyond the academic community. This study aims to introduce readers into other bibliometric and non-bibliometric (altmetric) indicators that provide a wider perspective about the impact any particular research outcome may have besides citations. From a geographic viewpoint, the documents published by AJVS between 2010-2019 were written by authors affiliated to institutions from 33 different countries, mostly from Chile (37%) and Mexico (24%). These two countries served as collaboration nodes for countries from America, Asia, Europe and Oceania. From an altmetric perspective, 59 documents published between 2010-2016 were mentioned at least once in one of the sources tracked, being the majority of them through social media. Of particular interest is one document that was used as a reference for a patent issued in 2017 by researchers that were not related to the document published in the journal. Unfortunately, data for the documents published between 2017-2019 were unavailable, probably due to issues with the journal title change. Nevertheless, it is fair to conclude that since research outputs have shown to have an impact well beyond academia, it may be time to reconsider how journals should be assessed in the near future.